Ruminal and abomasal impaction in breeding cows associated with the consumption of a deferred Megathyrsus maximus cv. Gatton pasture (FAVE Sección Ciencias Veterinarias, 2019)
Ruminal and abomasal impaction is a pathological condition of ruminants that occurs when they consume a food with very low digestibility, low protein and energy content. Ruminal and abomasal impaction was registered in breeding cows in the Argentina northwest grazing Megathyrsus maximus cv. Gatton. The clinical signs were anorexia, loss of body condition, recumbency and death. The clinical presentation of ruminal and abomasal impaction is well described in the bibliography but reports are scarce in Argentina.
Keywords: Impactation; cattle; Gatton panic